Identification of variety-specific ISSR markers in small cardamom (Elettaria cardamomum Maton.) - Jose, Sherin; Mathew, K. Mary; Rao, Y. S.; Kuruvilla, K. M.; Sudarshan, M. R. (Journal of Plantation Crops, 2019)
-----------